2023
DOI: 10.1108/ebr-11-2022-0224
|View full text |Cite
|
Sign up to set email alerts
|

A primer on integrated generalized structured component analysis

Abstract: Purpose The purpose of this paper is to present integrated generalized structured component analysis (IGSCA) as a versatile approach for estimating models that contain both components and factors as statistical proxies for the constructs. The paper sets out to discuss the how-tos of using IGSCA by explaining how to specify, estimate, and evaluate different types of models. The paper’s overarching aim is to make business researchers aware of this promising structural equation modeling (SEM) method. Design/met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…The standardized root mean residuals (SRMR) value for a properly model fit was zero or nearby (Hu & Bentler, 1999). The SRMR value in this study was 0.078 (N=157), indicating that the model fit was moderately acceptable (Hwang et al, 2023). R 2 values of 0.75 are considered substantial, 0.50 moderate and 0.25 weak (Hair et al, 2019).…”
Section: Structural Model Assessment and Hypotheses Testingmentioning
confidence: 63%
“…The standardized root mean residuals (SRMR) value for a properly model fit was zero or nearby (Hu & Bentler, 1999). The SRMR value in this study was 0.078 (N=157), indicating that the model fit was moderately acceptable (Hwang et al, 2023). R 2 values of 0.75 are considered substantial, 0.50 moderate and 0.25 weak (Hair et al, 2019).…”
Section: Structural Model Assessment and Hypotheses Testingmentioning
confidence: 63%
“…For adaptability, it was high (mean = 3.56), flexibility was moderate (mean = 3.42) and productivity was also moderate (mean = 3.34). The HTMT correlations in Table 2 measuring discriminant validity showed that all the values were below 0.90, which is the maximum, suggesting the existence of discriminant validity (Hwang et al, 2023). Therefore, the constructs independently measured the study variables.…”
Section: Measurement Modelsmentioning
confidence: 91%
“…For example, "the idea that PLS data may be used to validate a measurement model is a fabrication; the PLS path estimate cannot be utilized in null hypothesis significance testing." While PLS is "not a panacea," Hwang et al (2023) responded to these worries about this approach is "a substantial method that warrants a prominent place in any empirical researcher's statistical arsenal." Furthermore, even with complex sample sizes, PLS-SEM analysis yields statistically significant findings ) Sarstedt et al, 2022).…”
Section: Sample Adequacy and Analysis Strategymentioning
confidence: 99%